Avaliação do acolhimento com classificação de risco em serviço hospitalar de emergência - Bellucci Júnior, José Aparecido (2011)
Currently the quality of health care has become concerns of professionals working in this area because, among other factors, there is growing demand from users for improvements in the care provided. In Emergency Hospital Service (EHS), the main challenges facing the quality of care concern: overcrowding; fragmented labor process, conflict and power asymmetries, the service delay, low resolution and humane treatment, among others. It is worth noting that in addition to these problems, the high number of patients could be treated in primary healthcare because it is an aggravating factor for the occurrence of cooperative approach to user according to the order of arrival. Presented and the challenges associated with the need to serve all so warm and resolute in the shortest possible time, the Ministry of Health proposed the directive in 2004 with User Embracement with Risk Rating (UERR). In EHS, this guideline has as main objective to receive and classify the risk levels of the user's priorities based on the severity of each case. This methodological study of its kind, aimed to investigate the general management and Nursing User Embracement by Risk Rating in Emergency Hospital Service. It was developed through qualitative and quantitative approaches during the period October 2009 to April 2011, through five steps: analysis of publications on quality management in EHS; account of the role of a nurse in the process of implementation of the UERR, comparison of the two flow EHS care, construction and validation of an instrument to assess the UERR; assessment UERR EHS implanted in a hospital public education. Among the main results obtained in the steps of the study found that in the last ten years, the publications that deal about the role of nurses in the quality of EHS management focused on spreading the concepts of humane care and for the caregiver. Another result of this step was the realization of several articles which reported the UERR as an effective strategy to promote quality in EHS. Regarding the implementation process of the UERR in EHS has revealed that the nurse is primarily responsible for planning, monitoring and evaluation of this guideline. With respect to the flow analysis that the user has been observed that EHS has the UERR in care is more organized and professional accountability for the care and forging links with the user (client and family). Concerning the construction and validation of instruments for assessing the UERR, it is considered that the final instrument, consisting of 21 questions divided into the three dimensions of Donabedian Health Evaluation (Structure, Process and Outcome) is valid for content and appearance. Regarding the evaluation of the UERR through the application of the Assessment Instrument for nursing staff in a EHS Public Teaching Hospital, the three dimensions and the UERR as a whole were classified as Good. Specifically it is noteworthy that among the 21 items surveyed, seven were classified as Excellent, Good 4, 9 and 1 Regular Price list. We conclude that the guideline UEER is a major strategy used in the promotion of quality EHS because the service that operates in accordance with their service flows behaviors are more organized and determined as well as to highlight the presence of nursing management actions who value the humane care and caregiver. As to the evaluation of the UERR, it concludes that the use of quantitative tools to assess the structure, processes and outcomes of the UERR in a Public Teaching Hospital made it possible to quantify the views of employees, indicate the strengths and weaknesses of the policy in place and of guiding to improve the quality of each item evaluated.